Prediksi Kelulusan Pegawai Pemerintah Dengan Perjanjian Kerja Guru Menggunakan Metode Naive Bayes - Basirung Umaternate; Imam T. Umagapi; Yuyun, Yuyun; Hazriani, Hazriani (Ikatan Ahli Informatika Indonesia, 2023)
Recruitment and selection of ASN PNS and PPPK candidates to date has quite a high number of enthusiasts, and the selection process using the Computer Assisted Test (CAT) is the main requirement for passing the PNS or PPPK selection. Therefore, the researcher made this research using pre-existing data or called training data. Researchers used the Naïve Bayes method with 9 mutually independent attributes to determine graduation. Researchers also used Microsoft Excel and Weka supporting applications to test the accuracy of the Naïve Bayes method. Tests were carried out with 212 datasets consisting of 170 training data/training data and 42 test data/testing. The results of the Accuracy, Recall, and Precesion tests determine the graduation of Government Employees with Work Agreements (PPPK) for Teachers in Morotai Island Regency, 100% Accuracy, 100% Precision, 100% Recall, and the Area Under ROC (AUC) value is 1, which means 100% below The curve shows that the performance of the Naïve Bayes algorithm in capitalizing the classification of graduation data for Government Employees with Employment Agreements (PPPK) for Teachers in Puau Morotai Regency is very good.